7-chloro-4-(phenylselanyl) quinoline prevents dopamine depletion in a Drosophila melanogaster model of Parkinson's-like disease. - de Freitas Couto, S.; Araujo, S.M.; Bortolotto, V.C.; Poetini, M.R.; Pinheiro, F.C.; Santos Musachio, E.A.; Meichtry, L.B.; do Sacramento, M.; Alves, D.; La Rosa Novo, D.; Mesko, M.F.; Prigol, M. (Journal of trace elements in medicine and biology : organ of the Society for Minerals and Trace Elements., 2019)
Neurodegeneration in Parkinson's disease appears to be caused by multiple factors, including oxidative damage and an increase in acetylcholinesterase expression that can culminate in loss of dopaminergic neurons. A selenium-containing quinoline derivative, 7-chloro-4-(phenylselanyl) quinoline (4-PSQ), shows important pharmacological actions mainly attributed to its antioxidant and anticholinesterase properties. Thus, this study investigated the neuroprotective effect of 4-PSQ in a model of Parkinson's-like disease induced by rotenone (ROT) in Drosophila melanogaster and verified whether these effects are related to selenium levels. Adult flies were divided into: [1] control, [2] 4-PSQ (25??M), [3] ROT (500??M), and [4] 4-PSQ (25??M)?+?ROT (500??M) groups and exposed to a diet containing ROT and/or 4-PSQ for 7 days, according to their respective groups. Survival, behavioral, and ex vivo analyses were performed. Dopamine levels, reactive species levels (RS), lipid peroxidation (LPO), superoxide dismutase (SOD) and catalase (CAT) activity, and proteic thiol (PSH) and non-proteic thiol (NPSH) content in the head region were analyzed, while acetylcholinesterase (AChE) activity and selenium levels in the head and body regions were analyzed. 4-PSQ was able to reverse the ROT-induced deficits in flies, reestablish dopamine and selenium levels, reverse cholinergic deficits, improve motor function, and ameliorate mortality. Furthermore, 4-PSQ also reduced RS levels and LPO, and restored the activities of the antioxidant enzymes, SOD and CAT. Interestingly, a positive relationship between dopamine and selenium levels could be seen. Our results demonstrate the neuroprotective effect of 4-PSQ, and we suggest that the compound may act via different mechanisms, such as improving antioxidant defenses and consequently reducing oxidative damages, as well as having an anticholinesterase action, which together can prevent dopamine depletion, as these actions were correlated with the presence of selenium in the 4-PSQ molecule.